Applied anthropometry in ergonomic design for school furniture - Paschoarelli, Luis Carlos [UNESP]; da Silva, José Carlos Plácido [UNESP] (Taylor & Francis, 2011)
The socio-historical evolution of developed countries is based on several factors, and we can highlight the basic education of the population among them. Politics and institutional activity have involved all socioeconomic levels, and physical infrastructure issues are tangible examples of the educational achievements observed in such communities.